Fungi of the human eye: Culture to mycobiome. (April 2022) - Shivaji, Sisinthy; Jayasudha, Rajagopalaboopathi; Prashanthi, Gumpili Sai; Arunasri, Kotakonda; Das, Taraprasad
Abstract: The focus of the current review is multi-fold and compares the diversity and abundance of fungi on the ocular surface by the conventional culture-based method with the more sensitive, high throughput, culture-independent NGS method. The aim is to highlight the existence of a core ocular mycobiome and explore the transition of the ocular fungal microbiota from the normal eye to the diseased eye. PubMed, Google Scholar and Medline were used to search for publications and reviews related to cultivable fungi and the mycobiome of the normal and diseased eye. The conventional cultivable approach and the NGS approach confirm that the eye has its own mycobiome and several confounding factors (age, gender, ethnicity etc.) influence the mycobiome. Further, dysbiosis in the mycobiome appears to be associated with ocular diseases and thus impacts the health of the human eye. Considering that the mycobiome of the eye is influenced by several confounding factors and also varies with respect to the disease status of the eye there is a need to extensively explore the mycobiome under different physiological conditions, different ethnicities, geographical regions etc. Such studies would unravel the diversity and abundance of the mycobiomes and contribute to our understanding of ocular health. Research focused on ocular mycobiomes may eventually help to build a targeted and individualized treatment. Graphical abstract: Image 1 Highlights: Conventional cultivable and NGS methods confirm that the eye has its own mycobiome. Several confounding factors (age, gender, ethnicity etc.) influence the ocular mycobiome. The mycobiome of the eye varies with respect to the disease status of the eye. A need to explore the mycobiome of different regions of the eye. Ocular mycobiome studies may eventually help in personalised treatment.